A multi-gas approach to climate policy: With and without GWPs - Alan S. Manne; Richard G. Richels (Fondazione Eni Enrico Mattei (FEEM), 2000)
When dealing with multiple greenhouse gases, we need some way to establish equivalence among gases. The Intergovernmental Panel on Climate Change (IPCC) has suggested the use of global warming potentials (GWPs) for making such trade-offs. We begin by examining the implications of such an approach for mitigation policy. We then discuss several significant limitations of GWPs. These include their failure to reflect damages, their sensitivity to the choice of time horizon, and their insensitivity to both the choice of and proximity to a prescribed target. We then explore an alternative approach where the relative price of each gas is an endogenous output rather than an exogenous input into the analysis. Our findings yield some important insights for those concerned with climate change policy making, particularly with regard to the role of each gas in accomplishing a long-term objective.
Keywords: 330; Luftverschmutzung; Klimaschutz; Klimawandel; Umweltabkommen; Emissionshandel; Welt